THE CONNECTION BETWEEN LANGUAGE AND CULTURAL IDENTITY - Аkramova Dilnoza, Chirchik Stаtе Pеdаgоgicаl Univеrsity Tоurism fаculty Fоrеign lаnguаgе аnd litеrаturе:Еnglish. Sciеntific supеrvisоr: Abduramonova Diana Еnglish tеаchеr, Chirchik Stаtе Pеdаgоgicаl Univеrsity (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Indigenous languages are increasingly at risk of extinction due to the global dominance of major languages, urbanization, and changes in societal structures. However, oral tradition remains essential in preserving these languages, serving as a key means of passing down cultural knowledge, values, and identities. Through practices such as storytelling, songs, rituals, and oral histories, indigenous communities preserve their linguistic heritage across generations. This article examines the role of oral tradition in safeguarding indigenous languages, the challenges it encounters, and how modern technology and education can support its revitalization. It underscores the importance of these traditions in preserving not just language, but the cultural wealth of indigenous communities.